Comorbidity in Rheumatic Diseases - El Miedany, Yasser (Springer International Publishing : Imprint: Springer, 2017)
This book explores comorbidity in patients with rheumatic diseases and details both care and treatment options in standard clinical practice.Patients with rheumatic diseases are clinically complex, and the interplay of their disease activity with associated conditions may lead to increased morbidity and mortality. Recently there have been major advances in the management of rheumatic diseases, however, without addressing the potential comorbid conditions, including cardiovascular disease; pulmonary disease; and depression; outcomes remain poor. With its 19 chapters, covering the management of major rheumatic diseases (e.g. rheumatoid arthritis, systemic lupus erythematosus , and osteoarthritis), potential comorbidities and treatment recommendations, as well as possible interactions between conditions; this book addresses the gap between textbook medicine and day to day patients' care. Authors also discuss the new hot issue of the comorbidity index, comparing the standard tools to the recently developed indices and how they can assist the rheumatologists in determining disease burden, prognosis, and comorbidity probability. This book is an ideal clinical guide and reference that enables rheumatologists, internal medicine physicians, and residents to address the full clinical expression of these rheumatic diseases with views towards prevention or early management of comorbid conditions. .